2020
DOI: 10.1111/joor.12944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tongue‐strengthening training combined with a tablet personal computer game in healthy adults

Abstract: Background: Game-based training has been shown to improve behavioural motor learning in various medical fields including rehabilitation.Objectives: This study aimed to investigate the effects of a tablet PC (personal computer) game-based tongue training on tongue strength, thickness and compliance in healthy adults.Methods: This study recruited 30 healthy volunteers. Subjects were randomly assigned to two groups (n = 15/group). Group 1 performed game-based tongue training, and group 2 performed tongue resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
0
15
0
6
Order By: Relevance
“…In this systematic review, TP data with IOPI from subjects all over the world, including Asia, 19,21,39,40,48,51,52,66‐70 Oceania, 50 North America, 9,17,18,29‐32,34,45,53,58,71 South America 36,43,54 and Europe, 15,72 have been collected. All TP values measured using the JMS are in the Japanese studies 2‐4,7,14,16,20,22‐24,33,35,37,38,41,42,44,46,47,49,51,55‐57,59‐61,64,73‐83 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this systematic review, TP data with IOPI from subjects all over the world, including Asia, 19,21,39,40,48,51,52,66‐70 Oceania, 50 North America, 9,17,18,29‐32,34,45,53,58,71 South America 36,43,54 and Europe, 15,72 have been collected. All TP values measured using the JMS are in the Japanese studies 2‐4,7,14,16,20,22‐24,33,35,37,38,41,42,44,46,47,49,51,55‐57,59‐61,64,73‐83 .…”
Section: Discussionmentioning
confidence: 99%
“…TA B L E 2 Results of quality assessment for (a) analytical study according to NOS, and for (b) included randomised clinical trials (RCTs) and non-RCTs according to Cochrane Collaboration's tool for assessing risk of bias In this systematic review, TP data with IOPI from subjects all over the world, including Asia, 19,21,39,40,48,51,52,[66][67][68][69][70] Oceania, 50 North America, 9,17,18,[29][30][31][32]34,45,53,58,71 South America 36,43,54 and Europe, 15,72 have been collected. All TP values measured using the JMS are in the Japanese studies.…”
Section: F I G U R E 2 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hwang and others believe that the maximum ventilation volume decreases rapidly with the increase in age. The maximum ventilation of the elderly is reduced due to the reduction of the contractility of respiratory muscles, the weakening of the compliance of the lungs and thorax, the increase in respiratory resistance, and the reduction of sensitive excitability of the respiratory center [ 11 ]. Hwang and others said that the maximum ventilation of middle-aged and elderly women who have participated in Taijiquan for a long time shows an upward trend, and the vital capacity (VC), forced vital capacity (FEV1), and airway obstruction (FEV1/FVC) are significantly increased, indicating that Taijiquan exercise can increase respiratory reserve, delay the degradation of ventilator energy caused by aging, significantly improve pulmonary elastic retraction, improve respiratory muscle strength, increase oxygen uptake, and ensure the body's demand for oxygen.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2014, the National Center for Geriatric and Gerontology of Japan proposed oral frailty, a condition wherein changes in the oral condition are combined with decreased interest in the oral cavity and reduced mental and physical reserve capacity, resulting in increased oral vulnerability [4]. Early detection and appropriate intervention has also been found to prevent the progression of oral frailty, with several reports showing the efficacy of exercise training [5, 6]. Moreover, Tanaka et al [7] suggested that oral frailty is one of the risk factors for physical frailty.…”
Section: Introductionmentioning
confidence: 99%